A Survey on the applications of IoT: an investigation into existing environments, present challenges and future opportunities - Fahad Ghalib Abdulkadhim; Zhang Yi; Chengkai Tang; Mudassar Khalid; Samer Adulateef Waheeb (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In today’s digital environment, devices are able to interconnect and react to contextual data more than ever before: artificial intelligence is beginning to coordinate how data collected from sensors and de-vices within the network is analysed, and device ecosystems are replacing standalone devices to deliver solutions to the user. In this paper, the researcher explores current implementations of IoT that have led to positive outcomes for the user; but also, the challenges that remain in today’s applications. Moreover, ex-ploring these current barriers may be able to infer future applications capable of being deployed on a global scale